CATTLE TEMPERAMENT AND REPRODUCTIVE SUCCESS - R.K. Kasimanickam; V.R. Kasimanickam; C. Joseph (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Cattle temperament is defined as the fear-related behavioral responses when exposed to human handling. As cattle temperament worsens, their response to human contact or any other handling procedures becomes more pronounced. The agitated and/or aggressive response expressed by cattle with excitable temperament when exposed to human handling can be attributed to their fear and consequent inability to cope with this situation. In addition to altered behavior, temperamental cattle may also experience changes in their body physiology, and the hormones produced during this fearrelated stress reaction influence several factors, such as growth and health. Within the cattle industry, producers select cattle for temperament, primarily for safety reasons. However, our recent studies demonstrate cattle temperament may also have productive and economic implications to beef operations. Stress increases stress hormones such as cortisol levels and results in lowering the levels of reproductive hormones. Most cattlemen recognize that cattle under stress may not eat as well but may not know of its effect on reproductive behavior and physiology. This article will summarize our findings that could have an impact on the beef herd.